2010
DOI: 10.1159/000317102
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Infiltration Is Involved in Renal Interstitial Fibrosis in a Rat Model of Protein-Overload Nephropathy

Abstract: Aims: The present study investigated the relationship between mast cells (MCs) and the protein expression of stem cell factor (SCF) and transforming growth factor-β1 (TGF-β1) in the regions of renal interstitial fibrosis with protein-overload nephropathy, in order to provide a good animal model to study the mechanism of renal fibrosis induced by proteinuria. Methods: 60 male Sprague-Dawley rats were divided into a bovine serum albumin (BSA) group and a control group. The intensity of MCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…17 Moreover, mast cells have been reported to participate in the development of fibrosis. [10][11][12] Mast cells may promote fibrosis by inducing fibroblast proliferation, migration, contraction, and collagen production through the release of a range of stored cytokines such as TGF-β from mast cells that act in a paracrine fashion to stimulate fibroblasts. 18 Recently, it was shown that fibrosis in IgG4-related diseases is induced by cytokines (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…17 Moreover, mast cells have been reported to participate in the development of fibrosis. [10][11][12] Mast cells may promote fibrosis by inducing fibroblast proliferation, migration, contraction, and collagen production through the release of a range of stored cytokines such as TGF-β from mast cells that act in a paracrine fashion to stimulate fibroblasts. 18 Recently, it was shown that fibrosis in IgG4-related diseases is induced by cytokines (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Increased MC infiltration has been observed in various animal models of kidney fibrosis, including nephropathy induced by protein overload and the unilateral ureteral obstruction model . In a study conducted on MC‐competent vs MC‐deficient Ws/Ws rats, Miyazawa et al found that fibrosis occurring in conjunction with puromycin aminonucleoside‐nephrosis was not MC‐dependent.…”
Section: Mast Cells In Models Of Kidney Fibrosismentioning
confidence: 99%
“…[133137], inversely correlating with renal function. [135, 137, 138] Mast cell deficiency has been associated with decreased fibrosis. [135] Mast cells have also been associated with antifibrotic actions.…”
Section: Cellular and Molecular Mediatorsmentioning
confidence: 99%